Analysis of fiscal decentralization impact on community welfare in Jambi Province - M. Zahari; Syamsurijal Tan; Haryadi Haryadi; Syaparuddin Syaparuddin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The fiscal decentralization policy has made local governments have the authority to generate income and manage regional finance independently for public services and public welfare. This study aims to: 1) Analyze the degree of fiscal decentralization in Jambi Province; 2) Analyzing community welfare proxied from the human development index in Jambi Province; 3) Analyzing the impact of fiscal decentralization on the welfare of the community in Jambi Province. This study using panel data, a combination of time series data in 2010-2016 and cross section 11 districts/cities in Jambi Province. The method of data analysis is descriptive analysis and panel data regression analysis approach, namely the fixed effect model (FEM). Hypothesis testing uses the F test statistic and the statistical t test. The results showed that: 1) The degree of fiscal decentralization, namely the ratio of district own source revenue (PAD) to total regional income (TPD) in each district/city in Jambi Province was relatively relatively low, whereas for Jambi Province it was in good category; 2) Community welfare as illustrated by the human development index in each district/city including Jambi Province is still in the moderate category, except Jambi City (76.14) and Sungai Penuh City (73.35) are categorized as high; 3) Fiscal decentralization has a positive and significant impact on improving community welfare. it means that the better the implementation of fiscal decentralization, the higher the level of community welfare.